Transcultural realities interdisciplinary perspectives on cross-cultural relations - Milhouse, Virginia Hall, 1950-; Asante, Molefi Kete, 1942-; Nwosu, Peter; Sage eBooks (Thousand Oaks, Calif. ; London : Sage, 2001)
This text challenges the quantitative, social science perspective on intercultural communication by examining critical issues from diverse perspectives. Key topics include historical and religious perspectives; racial and ethnic issues; cross-cultural adaptation; and methods of researching 'other' cultures.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Intercultural communication; Cross-cultural orientation; Cultural relations; Electronic books